Možnosti uporabe hipnoze in hipnoterapije v poklicni in zaposlitveni rehabilitaciji - Fulder, Bojana (Rehabilitacija (Ljubljana), 2014)
The paper presents some possibilities of using hypnosis and hypnotherapy in occupational and vocational rehabilitation. The problems of our users are becoming increasingly complex, so we are looking for more effective ways, techniques and methods that make it easier to pursue the objectives of rehabilitation. Hypnotherapy in combination with cognitive behavioural therapy is extremely effective in dealing with various psychosomatic disorders, anxiety, phobias, depression, pain relief, releasing muscle tension, eliminating insomnia reducing body weight and overcoming addiction.
Keywords: Cognitive Therapy; hipnoterapija; hipnoza; Hypnosis; hypnotherapy; kognitivna terapija; occupational rehabilitation; poklicna rehabilitacija; Rehabilitation, Vocational; zaposlitvena rehabilitacija